ESTUDO DA RELAÇÃO ENTRE OS NÍVEIS DE ÁCIDO ÚRICO E SÍNDROME METABÓLICA EM MULHERES PÓS-MENOPAUSA - Gelatti, Gabriela T.; Kal, Jerry B.; Oliveira, Karla R. d.; Berlezi, Evelise M. (Salão do Conhecimento, 2013)
Resumo